Propuesta psicopedagógica basada en la taxonomía de Barret para estimular el avance de la comprensión lectora en estudiantes universitarios de primer ciclo de la Carrera de Derecho de la Universidad Nacional de Loja, 2024- 2025 - Flores Quito, Paola Mishelle (2025)
The Curricular Integration Project aimed to design a psychopedagogical proposal based on Barrett's Taxonomy to stimulate reading comprehension development in first-year law students at the National University of Loja. This study analyzed the results of a previous research study conducted with students using the Instrument for Assessing Reading Comprehension in University Students (ICLAU). The findings showed low levels of reading comprehension according to Barrett's Taxonomy, highlighting the need for targeted intervention. The results of the Survey on Reading Comprehension Levels According to University Subjects (ENCLAU), administered to teachers, were also used as a reference. This survey revealed that some subjects require strengthening certain levels of reading comprehension more than others. In this regard, in the Law course, 100% of students were found to be critical and appreciative, while in Introduction and History of Law and Research Methodology, the literal and reorganizational levels reached 100%. In Legal Ethics, the reorganizational level reached 87.5%, and in Legal Sociology, 100% were found for the literal and appreciative levels. These results allowed us to identify the areas in which reading comprehension needs to be strengthened according to the requirements of each subject. Methodologically, the research adopted a quantitative, descriptive, and non-experimental approach. Based on the findings, the psychopedagogical proposal was designed around the Oral and Written Expression course. This choice will strengthen reading comprehension skills, promoting students' academic development